A CRUCIAL: CLUSTER AND FACTOR ANALYSIS APPROACH TO CLASSIFY ZIKA VIRUS DATASETS IN USA AND INDIA - PARITALA, VENU; THUMMALA, HARSHA (Innovare Journal of Medical Sciences, 2022)
Objective: The aim of this research is to analyze the relationships between the counts of cases and the deaths due to Zika Virus in USA, India, countries that are severely affected from this pandemic disease. Methods: Cluster correlation is used to determine the relationships among these countries. Then, factor analysis is applied to categorize these countries based on their relationships. R (reproducible research with R and R studio, second edition, 2018) is server which is hosted in a cloud platform. For the development of analytical pipeline, various R packages were used. Results: The novel analysis which results in factor analysis it reports the count of positive cases in hugely Kerala and Trivandrum in India and American Samoa, Puerto Rico, and us Virgin Islands territories in the USA. Conclusion: However, as fast as viruses spread, the detection of pandemics, and taking early, these analyses help to suggest virus affected states in disparate countries, then government take care of them.